Hamka's Critique on Sigmund Freud's Theory of Psychoanalytic - Dedy Irawan; Fadhil Sofian Hadi; Usamah Abdurrahman (TSAQAFAH, 2023)
AbstractThis paper is Hamka's critique of Sigmund Freud on psychoanalysis. For Freud, human life is driven by sexual desire from birth. With this, causing the loss of the divine nature in humans. Freud views the human soul as a creature that is only controlled by the sex libido which tends to be pessimistic. By using literature review and using qualitative data. The result found a different view with Hamka. Hamka denies that humans are only controlled by sexual libido. In his interpretation of al-Azharnya Hamka emphasized that in religion (Islam) humans were created by Allah with the best creature, both outward and inward form, body shape and life. Therefore Hamka explained that the soul (an-nafs) as the essence of human beings is divided into three parts. First, nafsul amarah bissiu’. Second, nafsul lawwamah, and nafsul mutmainnah. These three forms of an-nafs were never explained by Freud and even forgotten. On the other side, Freud views that religion is the cause of the emergence of neuroses that threaten human life. Therefore, Hamka emphasized that Freud's psychoanalysis was seen as not touching the aesthetic value (in) the human soul, thus creating arid mentality for humans.Keywords: Psychoanalysis, Sigmund Freud, mysticism, Hamka, Islam AbstrakMakalah ini merupakan kritik Hamka atas Sigmund Frued tentang psikoanalisah. Bagi Frued, manusia hidup di dorong oleh keinginan seksualnya sejak lahir. Dengan ini, menyebabkan hilangnya sifat ketuhanan dalam diri manusia. Frued memandang jiwa manusia sebagai makhluk yang hanya dikendalikan oleh libido sex yang cenderung pesimistis. Dengan menggunakan kajian pustaka dan menggunakan data kualitatif. Hasilnya ditemukan pandangan yang berbeda dengan Hamka. Hamka membantah bahwa manusia hanya dikendalikan oleh libido sex. Dalam tafsinya al-Azharnya Hamka mempertegas bahwa di dalam agama (Islam) manusia diciptakan oleh Allah dengan sebaik-baik bentuk, baik bentuk lahir maupun batin, bentuk tubuh dan nyawanya. Karenanya Hamka menjelaskan bahwa jiwa (an-nafs) sebagai esensi dari manusia menjadi 3 bagian. Pertama, nafsul amarah bissu’. Kedua, nafsul lawwamah, dan nafsul mutmainnah. Ketiga bentuk an-nafs tidak pernah dijelaskan oleh Frued bahkan terlupakan. Sehingga Frued memandang bahwa agama merupakan penyebab dari timbulnya neurosis yang mengancam kehidupan manusia. Karenanya, Hamka mempertegas bahwa psikoanalisah Frued dipandang tidak menyentuh nilai esetoris (dalam) jiwa manusia sehingga menciptakan kegersangan jiwa bagi manusia.     Kata kunci: Psikoanalisah, Sigmund Freud, tasawuf, Hamka, Islam